VOIP End-To-End Security using S/MIME and a Security Toolbox (Global Journal of Computer Science and Technology, 2014)
Voice Over Internet Protocol (VOIP) is a rapidlygrowing Internet service for telephone communication. However, while it offers a number of cost advantages over traditional telephone service, it can pose a security threat, especially when used over public networks. In the absence of sufficient security, users of public networks are open to threats such as identity theft, man-in-the-middle attack, interception of messages/eavesdropping, DOS attacks, interruption of service and spam. S/MIME adds security to the message itself and can be used to provide end-to-end security to SIP. S/MIME can also offer confidentiality or integrity, or both, but it does not provide any anti-replay protection. However, we propose to use a unified architecture for the implementation of security protocols in the form of a security toolbox system. It will prevent an attack against anti-replay.
Keywords: S/MIME; SIP; IPSEC; replay attack; SDP